Cisplatin impairs fluid and electrolyte absorption in rat small intestine: a role for 5-hydroxytryptamine. Issue 2 (1st February 1999) - Bearcroft, C P; Domizio, P; Mourad, F H; André, E A; Farthing, M J G
Abstract : Background: The antineoplastic drug cisplatin has been widely used for the treatment of cancer in humans but its use has been limited by vomiting and diarrhoea. Cisplatin releases 5-hydroxytryptamine into the gut which is thought to be the major mediator of cisplatin induced vomiting. Aim: To determine whether cisplatin affects fluid and electrolyte transport in rat jejunum and whether this change can be modulated by the 5-hydroxytryptamine3 receptor antagonist, ondansetron. Methods: Jejunal perfusion in rats in vivo was performed one hour after intraperitoneal cisplatin (5 and 10 mg/kg) administration. The effect of pretreatment with subcutaneous ondansetron 300 μg/kg was investigated. Results: Median net fluid absorption after cisplatin 10 mg/kg (67 μl/min/g dry intestinal weight (interquartile range 46 to 100); n = 15) was reduced compared with controls (120 (107 to 151) μl/min/g; n = 13; p<0.001). Ondansetron reversed the impairment of jejunal fluid absorption produced by cisplatin to normal (161 (130 to 176) μl/min/g; n = 11; p<0.001). Electrolyte movement paralleled fluid movement. Jejunal histological examination of sections from cisplatin treated animals showed villus damage, which was not prevented by pretreatment with ondansetron. Conclusion: These findings suggest that diarrhoea during cisplatin therapy may be due to altered fluid transport in the small bowel. The reversal of fluid transport to normal in the presence of a 5-hydroxytryptamine3 receptor antagonist suggests that 5-hydroxytryptamine is a local mediator in the small intestine.